2017
DOI: 10.1055/s-0042-122713
|View full text |Cite
|
Sign up to set email alerts
|

Back Pain in Adolescent Athletes: Results of a Biomechanical Screening

Abstract: The aim was to use a short biomechanical test battery to screen adolescent athletes with and without back pain to reveal relevant and possibly preventable deficits. 1 559 adolescent athletes (m/f 945/614; 13.2±1.6y) were included. Back pain was assessed (1–5: 1=no pain; 5=maximum pain) for dichotomous categorization into back pain (BP: pain>2, n=113), healthy (NBP All : pain=1, n=1 213) and matched healthy (NBP matched : pain=1, n=113) athletes. Athletes performed stability, performance (jumps) and trunk stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Of the 60 articles, most were surveyed in athletes in Germany [14,18,49,[52][53][54][55][56][57][58][59][60][61][62], in Sweden [3,[63][64][65][66], and in Iran [36,37,[67][68][69]. Moreover, also in Norway [11,70,71], Poland [72][73][74], United States [50,51,75], the Netherlands [76,77], Belgium [78], Switzerland [12,79], Finland [80,81], Australia [82,83], Spain [84,85], Saudi Arabia [86,87], Estonia [88], Serbia [89], New Zealand [90], Ukraine [91], China…”
Section: Resultsmentioning
confidence: 99%
“…Of the 60 articles, most were surveyed in athletes in Germany [14,18,49,[52][53][54][55][56][57][58][59][60][61][62], in Sweden [3,[63][64][65][66], and in Iran [36,37,[67][68][69]. Moreover, also in Norway [11,70,71], Poland [72][73][74], United States [50,51,75], the Netherlands [76,77], Belgium [78], Switzerland [12,79], Finland [80,81], Australia [82,83], Spain [84,85], Saudi Arabia [86,87], Estonia [88], Serbia [89], New Zealand [90], Ukraine [91], China…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the following assessments are performed at baseline and at follow-up 3 months later: functional assessments such as the 6-minute walk test (6MWT) [ 20 ] for physical capacity, the Timed Up and Go Test (TUG) [ 21 ], the Stair Ascend Test [ 22 ], the Five-Times-Sit-to-Stand Test [ 23 ] for balance, strength and mobility, the questionnaires Short Form 36 (SF-36) [ 24 ] for health-related quality of life, International Physical Activity Questionnaire (IPAQ) [ 25 ] for the level of physical activity and the Western Ontario and McMaster Universities Arthritis Index (WOMAC) [ 26 ] for pain and stiffness. Measures of function include the assessment of the postural control during double-footed and one-leg stance [ 27 ] for left and right leg (barefoot, hands to the hip, view straight forward) for 30 s on a force plate (Amti OR6-6, Advanced Mechanical Technology, Inc. Watertown, MA, USA) as well as gait analysis during over-ground walking (10 trials) with self-selected velocity using a 3D-motion analysis system (12 cameras, Vicon MX; 200 Hz; Vicon Ltd., Oxford, UK) and a kinematic Plug-in Gait lower body model (Vicon Nexus) [ 28 ] (see Fig. 2 for the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) Figure that the trial follows).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, during a single-leg squat exercise, Borujeni and Yalfani 35 reported poor postural control in athletes with CLBP, which in turn, was improved after an 8-week program of respiratory muscle training combined with weightlifting and powerlifting exercises. 35 Contrarily, Mueller et al, 36 evaluating COP parameters during the one-legged stance task, reported no differences between athletes with and without back pain.…”
Section: Comparison Between Groupsmentioning
confidence: 99%